Global Health Research in an Unequal World Ethics Case Studies from Africa - Aellah , Gemma (CABI, 2016)
This book is a collection of fictionalised case studies of everyday ethical dilemmas and challenges, encountered in the process of conducting global health research in places where the effects of global, political and economic inequality are particularly evident. It is a training tool to fill the gap between research ethics guidelines, and their implementation 'on the ground'. The case studies, therefore, focus on 'relational' ethics: ethical actions and ideas that emerge through relations with others, rather than in regulations.